Irrigation policy and management in Southeast Asia (Los Banos, Philippines, 1978)
This book divides 5 parts. Part 1 is the interpretative summary, which identifies the main themes that emerged from the seminar and highlights the most important issues discussed. Part 2 describes selected strategies being followed by various Southeast Asia countries in planning and designing irrigation infrastructure. Part 3 deals with the management, operation, and maintenance of irrigation systems. Part 4 covers economic issues in irrigation, it includes analyses of the economic performance of various types of irrigation projects and assessments of policies for secury repayment of irrigation investment. Part 5 deals with irrigation organization and farmer's behavior
Keywords: Irrigation management,Water supply